2007
DOI: 10.1016/j.mrfmmm.2006.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin disassembly and reassembly during DNA repair

Abstract: Current research is demonstrating that the packaging of the eukaryotic genome together with histone proteins into chromatin is playing a fundamental role in DNA repair and the maintenance of genomic integrity. As is well established to be the case for transcription, the chromatin structure dynamically changes during DNA repair. Recent studies indicate that the complete removal of histones from DNA and their subsequent reassembly onto DNA accompanies DNA repair. This review will present evidence indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 107 publications
(132 reference statements)
2
34
0
Order By: Relevance
“…17,133 Even though post-repair chromatin reassembly occurs mostly with new histones, a portion of the old evicted histones could be recycled and in such a case, Asf1 could exercise the storage function of evicted histones, given its known role in chromatin disassembly. 136 In this context, it has been suggested that Asf1 has a role in chromatin disassembly during DNA repair. 136 Consistent with the idea of the existence of specific mechanisms for restoring epigenetic marks, DNA methyltransferase DNMT1 is recruited to DNA repair sites through its interaction with PCNA.…”
Section: Restoring Chromatin Structurementioning
confidence: 99%
See 4 more Smart Citations
“…17,133 Even though post-repair chromatin reassembly occurs mostly with new histones, a portion of the old evicted histones could be recycled and in such a case, Asf1 could exercise the storage function of evicted histones, given its known role in chromatin disassembly. 136 In this context, it has been suggested that Asf1 has a role in chromatin disassembly during DNA repair. 136 Consistent with the idea of the existence of specific mechanisms for restoring epigenetic marks, DNA methyltransferase DNMT1 is recruited to DNA repair sites through its interaction with PCNA.…”
Section: Restoring Chromatin Structurementioning
confidence: 99%
“…136 In this context, it has been suggested that Asf1 has a role in chromatin disassembly during DNA repair. 136 Consistent with the idea of the existence of specific mechanisms for restoring epigenetic marks, DNA methyltransferase DNMT1 is recruited to DNA repair sites through its interaction with PCNA. 145 DNMT1 may preserve cytosine methylation patterns in the newly synthesized DNA, and so participates in the conservation of epigenetic information after repair of DNA damage.…”
Section: Restoring Chromatin Structurementioning
confidence: 99%
See 3 more Smart Citations